COMPENSATORY GROWTH IN ALPACAS: EFFECT OF DIFFERENT ENERGY RESTRICTION LEVELS - Olazábal L., Juan (2009)
The present study was carried out to evaluate the compensatory growth (CG) in alpacas as the effect of a energy restriction period, measured in terms of body weight gain, feed intake, feed conversion and recover index. Twenty weaned female alpacas underwent a restricted feed intake phase and a compensatory phase of 60 days each. Treatments during the restriction phase were: No restriction level (NR): 3.5% dry matter (DM) of body weight (BW), Moderate restriction level (Rmod): 2.5% DM of BW, Medium restriction level (Rme): 1.8% DM of BW, High restriction level (RH): 1.08% DM of BW. The animals were feed ad libitum with the same type of feed during the compensatory phase. The growth rate during the compensatory phase varied according to the level of feed restriction, being higher in animals under Rmod, followed by Rme and RH. During the CG period, alpacas with feed restriction showed higher feed intake and better feed conversion; furthermore, the higher growth rates, better conversion rates and recover index were observed during the first period of the compensatory phase.